Presenting the relationship model of mindfulness, dark personality and academic competence on mental rumination with the mediating role of academic self-efficacy and the relationship between the teacher and students of the second year of high school - reza fathi; somayeh negahdari; mohammad hasan seyf (مطالعات روانشناسی تربیتی)
The aim of this study was to present a model of relationships between mindfulness, dark personality and academic competence on mental rumination with the mediating role of students' academic self-efficacy. The statistical population of this study included high school students in Shiraz, of which 382 Samples were selected. The instruments used in this study include standard questionnaires of teacher interaction with students Murray and Zovich (2010), Ginger and Morgan (1999) academic self-efficacy, Johnson and Webster's Dark Personality Triangle (2010), Huxma and Murrow (1991), rumination, Freiburg mindfulness was the short form of Ghasemi Jobneh et al. (2015), Deperna and Elliott (1999) academic competence. The collected data were analyzed by path analysis method. The results showed that the most direct effect of dark personality on rumination (0.25) and the least direct effect of mindfulness on self-efficacy (0.17) and mindfulness on rumination (-0.17), academic competence on Academic self-efficacy (0.17) and teacher-student interaction on academic self-efficacy (0.17). In addition, the most indirect effect is related to the effect of dark personality on rumination (0.04), academic competence on self-efficacy (0.04). And academic competence on rumination (-0.04) and the least indirect effect is related to the effect of mindfulness on rumination (-0.03) and teacher interaction with students on rumination (-0.03). Finally, the most The total effect is related to the effect of dark personality on rumination (0.29) and the lowest total effect is related to the effect of teacher interaction with students on rumination (-0.03).